PDCD10-Deficiency Promotes Malignant Behaviors and Tumor Growth via Triggering EphB4 Kinase Activity in Glioblastoma - Wan, Xueyan; Saban, Dino Vitali; Kim, Su Na; Weng, Yinlun; Dammann, Philipp; Keyvani, Kathy; Sure, Ulrich; Zhu, Yuan (Frontiers in Oncology, 2020)
We previously reported an angiogenic and tumor-suppressor-like function of programmed cell death 10 (PDCD10) in glioblastoma (GBM). However, the underlying mechanism remains to be elucidated. We hypothesized that loss of PDCD10 activates GBM cells and tumor progression via EphB4. To this end, PDCD10 was knocked down in U87 and T98g by lentiviral mediated shRNA transduction (shPDCD10). GBM cell phenotype in vitro and tumor growth in a mouse xenograft model were investigated in presence or absence of the treatment with a specific EphB4 kinase inhibitor NVP-BHG712 (NVP). We demonstrated that knockdown of PDCD10 in GBM cells significantly upregulated the mRNA and protein expression of EphB4 accompanied by the activation of Erk1/2. EphB4 kinase activity, reflected by phospho-EphB4, significantly increased in shPDCD10 GBM cells and in tumors derived from shPDCD10 GBM xenografts, which was abolished by the treatment with NVP. Furthermore, NVP treatment significantly suppressed PDCD10-knockdown mediated aggressive GBM cell phenotype in vitro and extensive tumor cell proliferation, the tumor neo-angiogenesis and a quick progression of tumor formation in vivo. In summary, loss of PDCD10 activates GBM cells and promotes tumor growth via triggering EphB4. Targeting EphB4 might be an effective strategy particularly for the personalized therapy in GBM patients with PDCD10-deficiency.